The Disappeared: images of the environment at Freetown's urban margins. - Hoffman, Danny (Visual Studies, 2007)
'The Disappeared' is a small collection of images documenting the deforestation of the mountain range outside Freetown, the capital of Sierra Leone. Aesthetically these images are inspired by West African photographic practices and represent an alternative ethnography of the recent war's impact on this region. The article outlines the dynamics of deforestation in the region but argues that the traditional realist aesthetic of documentary photography is no longer a compelling way to represent this issue. Beginning with a West African (particularly Yoruba) notion of the 'truth' of the photographic image, 'The Disappeared' charts a different path for engaged visual ethnography and for intervening in the politics of visual representation.